Alterations in Polyadenylation and Its Implications for Endocrine Disease - Rehfeld, Anders; Plass, Mireya; Krogh, Anders; Friis-Hansen, Lennart (Frontiers in Endocrinology, 2013)
Introduction Polyadenylation is the process in which the pre-mRNA is cleaved at the poly(A) site and a poly(A) tail is added - a process necessary for normal mRNA formation. Genes with multiple poly(A) sites can undergo alternative polyadenylation, producing distinct mRNA isoforms with different 3’ untranslated regions (3’ UTRs) and in some cases different coding regions. Two thirds of all human genes undergo alternative polyadenylation. The efficiency of the polyadenylation process regulates gene expression and alternative polyadenylation plays an important part in post-transcriptional regulation, as the 3’ UTR contains various cis-elements associated with post-transcriptional regulation, such as target sites for microRNAs and RNA-binding proteins. Implications of alterations in polyadenylation for endocrine disease Alterations in polyadenylation have been found to be causative of neonatal diabetes and IPEX (immune dysfunction, polyendocrinopathy, enteropathy, X-linked) and to be associated with type I and II diabetes, pre-eclampsia, fragile X-associated premature ovarian insufficiency, ectopic Cushing syndrome and many cancer diseases, including several types of endocrine tumor diseases. Perspectives Recent developments in high-throughput sequencing have made it possible to characterize polyadenylation genome-wide. Antisense elements inhibiting or enhancing specific poly(A) site usage can induce desired alterations in polyadenylation, and thus hold the promise of new therapeutic approaches. Summary This review gives a detailed description of alterations in polyadenylation in endocrine disease, an overview of the current literature on polyadenylation and summarizes the clinical implications of the current state of research in this field.